Newton-raphson method to solve systems of non-linear equations in VANET performance optimization - Siti Asilah Yah; Naimah Yaakob; Mohamed Elshaikh Elobaid; Ong Bi Lynn; R. Badlishah; Wan Aida Nadia Wan Abdullah (Institute of Advanced Engineering and Science, 2019)
Nowadays, Vehicular Ad-Hoc Network (VANET) has got more attention from the researchers. The researchers have studied numerous topics of VANET, such as the routing protocols of VANET and the MAC protocols of VANET. The aim of their works is to improve the network performance of VANET, either in terms of energy consumption or packet delivery ratio (PDR) and delay. For this research paper, the main goal is to find the coefficient of a, b and c of three non-linear equations by using a Newton- Raphson method. Those three non-linear equations are derived from a different value of Medium Access Control (MAC) protocol's parameters. After that, those three coefficient is then will be used in optimization of the VANET in terms of energy, PDR, and delay.